Museums, health and wellbeing research: co-developing a new observational method for people with dementia in hospital contexts. (May 2018) - Morse, Nuala; Chatterjee, Helen
Aims: The aim of this article is to present a new observational tool for assessing the impacts of museum object handling for people with moderate-to-severe dementia in hospital settings, focusing on wellbeing, social interaction, level of engagement and agitation. This article presents a four-step approach to collaboration towards co-developing the tool, which involved a range of academics, museums professionals, and health and social care partners, and describes the process of integrating multiple perspectives towards common research methodologies. Methods: The research team organised a series of meetings and workshops with museum and healthcare partners to identify commonly used assessments and their perspectives on the objectives and possible outcomes of museum object handling activities. These were integrated with findings from a review of current conceptualisations of engagement in people with dementia (PWD) to produce a fit-for-purpose video evaluation method of the health and wellbeing impacts of the museum object handling programmes. Results: This article presents the Museum Engagement Observation Tool for use in hospital settings for people with moderate-to-severe dementia. Conclusion: This article suggests that collaborative approaches can inform the development of future methods for creative health research and evaluation initiatives and to support this, it outlines the process of development of a new observational tool for people with dementia.